DETEKSI BAKTERI PATOGEN TERBAWA BENIH AKOR (ACACIA AURICULIFORMIS A. CUNN. EX BENTH.) - Suharti, Tati; Joko, Tri; Arwiyanto, Triwidodo (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Detection of seed-borne pathogenic bacteria of northern black wattle (Acacia auriculiformis A. Cunn. ex Â enth.). Intensive research of seed-borne pathogen of A. mangium and A. crassicarpa which have been established in industrial timber estate (HTI) was undertaken in Indonesia, while plantings development of northern black wattle have recently been established in the 1990s. Very limited information available on northern black wattle diseases especially seed-borne diseases. The objectives of this study were to identify seed-borne pathogenic bacteria of northern black wattle and the effects on seed germination. Methods for the isolation of bacteria were by seed soaking, seed griding, blotter test, growing-on test on paper and soil. Identification of bacteria by PCR used 63F/1387R primer. The results showed that seed-borne bacteria of northern black wattle were Paenochrobactrum sp., Ralstonia sp., Burkholderia cepacia complex, Pseudomonas stutzeri, Acinetobacter sp., Alcaligenes faecalis, Salmonella bongori, Escherichia hermannii while pathogenic bacteria cause seedling leafspot were Micrococcus luteus and Burkholderia cepacia complex. Burkholderia cepacia complex, A. faecalis, Acinetobater sp., P. stutzeri, S. bongori and Ralstonia sp. reduced seed germination and increased rotten seed, suggested that they were the pathogenic bacteria of northern black wattle seed. Ralstonia sp. significantly increased the percentage of rotten seed and decreased shoot length and root length. P. stutzeri and S. bongori significantly inhibited the root growth. Paenochrobactrum sp. and E. hermannii were assumed as pathogen with weak virulence due to seed germination, the percentage of rotten seed and vigour index were relatively similar to untreated seed.